Peran World Wide Fund for Nature dalam Menangani Kejahatan Transnasional di Bidang Lingkungan: Kasus Perburuan dan Perdagangan Ilegal Orangutan Tahun 2014-2018 - Teuku Haris Syahputra; Tri Cahyo Utomo (Journal of International Relations Diponegoro, 2019)
Orangutan is an endangered species from Indonesia. Orangutans faced problems include poaching and illicit trade. On the islands of Sumatra and Kalimantan, two islands in which are orangutan natural habitats, conflicts between orangutans and humans continue to occur. Orangutans were hunted and traded illegally, which let it on the verge of extinction. To prevent this, various international non-governmental organizations (NGO) such as World Wide Fund for Nature (WWF), are keen to take an action. This study analyzes the role of WWF in orangutan protection activities through the perspective of the World Bank in defining NGOs. The perspective explains that the role of NGOs is divided into two, namely the operational role and the advocacy role. WWF's operational role can be seen from projects such as the Wildlife Crime Initiative (WCI) and field programs such as direct supervision of orangutan habitat in various national parks on the islands of Sumatra and Kalimantan. Meanwhile, WWF's advocacy role is in the form of awareness raising activities targeting the government and the citizens. The result of this study, WWF's role in protecting orangutans increase in orangutan populations at the end of the study period.